The long voyage : selected letters of Malcolm Cowley, 1915-1987 - Cowley, Malcolm, 1898-1989 (Harvard University Press, 2014)
Critic, poet, editor, chronicler of the Lost Generation, elder statesman of the Republic of Letters, Malcolm Cowley (1898-1989) was an eloquent witness to American literary and political life. His letters, mostly unpublished, provide a self-portrait of Cowley and his time and make possible a full appreciation of his long, varied career.